2016
DOI: 10.1111/dom.12644
|View full text |Cite
|
Sign up to set email alerts
|

L‐arginine promotes gut hormone release and reduces food intake in rodents

Abstract: AimsTo investigate the anorectic effect of L‐arginine (L‐Arg) in rodents.MethodsWe investigated the effects of L‐Arg on food intake, and the role of the anorectic gut hormones glucagon‐like peptide‐1 (GLP‐1) and peptide YY (PYY), the G‐protein‐coupled receptor family C group 6 member A (GPRC6A) and the vagus nerve in mediating these effects in rodents.ResultsOral gavage of L‐Arg reduced food intake in rodents, and chronically reduced cumulative food intake in diet‐induced obese mice. Lack of the GPRC6A in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…Furthermore, the low number of study participants might be one reason for the reduced effect size of the ad libitum energy intake from the standardized breakfast of 0.17 MJ, in comparison to the expected effect size of 0.47 MJ. Overall, these results indicate a satiating effect of wheat protein hydrolysate and l ‐arginine, which is in accordance with current literature, stating that protein intake in human and l ‐arginine in rodents, induces a decrease in energy intake.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the low number of study participants might be one reason for the reduced effect size of the ad libitum energy intake from the standardized breakfast of 0.17 MJ, in comparison to the expected effect size of 0.47 MJ. Overall, these results indicate a satiating effect of wheat protein hydrolysate and l ‐arginine, which is in accordance with current literature, stating that protein intake in human and l ‐arginine in rodents, induces a decrease in energy intake.…”
Section: Discussionsupporting
confidence: 92%
“…Secretion of gastric acid facilitates the degradation of proteins into amino acids, which may contribute to the satiating effect of proteins. Dietary l ‐arginine, i.e., has been shown to reduce energy intake in rodents and to delay and inhibit gastric emptying . Furthermore, we recently demonstrated that l ‐arginine stimulated mechanisms of GAS and increased the release of serotonin in a parietal cell model.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, l-Arg is one of the most effective anorectic amino acids in rats (Jordi et al, 2013). Alamshah et al (2016) showed that increased l-Arg intake induced anorexia in rodents.…”
Section: Introductionmentioning
confidence: 99%